Competition in a pure world of Internet telephony - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2007)
From the angle of competition policy, Voice over IP looks like a panacea. It not only brings better service, but it also increases competitive pressure on former telecommunications monopolists. This paper points to the largely overlooked downside. In a pure world of Internet telephony, there would be no charge for individual calls, nor for telephony, as distinct from other services running over the uniform network. Specifically, establishing property rights for either of these would be costly, whereas these property rights were automatic and free of charge in switched telephony. Giving voice over IP providers classic telephone numbers would enhance systems competition with switched telephony. But this would make it more difficult for clients to swap providers. The anti-competitive caller pays principle would extend to IP telephony.
Keywords: D23; D43; H41; K21; K23; L13; L15; L43; L86; 620; property right; non-linear pricing; pure bundling; club good; cross-subsidisation packet switched telephony; CTI; Wettbewerb; Eigentumsrecht; Telekommunikationsgebühr; Welt